An In Vitro Assessment of Acoustic Radiation Force Impulse Imaging for Visualizing Cardiac Radiofrequency Ablation Lesions: Ablation Lesion Quantification with ARFI Imaging - Eyerly, Stephanie A. (2009)
INTRODUCTION: Lesion placement and transmurality are critical factors in the success of cardiac transcatheter radiofrequency ablation (RFA) treatments for supraventricular arrhythmias. This study investigated the capabilities of catheter transducer based acoustic radiation force impulse (ARFI) ultrasound imaging for quantifying ablation lesion dimensions. METHODS AND RESULTS: RFA lesions were created in vitro in porcine ventricular myocardium and imaged with an intracardiac ultrasound catheter transducer capable of acquiring spatially registered B-mode and ARFI images. The myocardium was sliced along the imaging plane and photographed. The maximum ARFI-induced displacement images of the lesion were normalized and spatially registered with the photograph by matching the surfaces of the tissue in the B-mode and photographic images. The lesion dimensions determined by a manual segmentation of the photographed lesion based on the visible discoloration of the tissue were compared to automatic segmentations of the ARFI image using two different calculated thresholds. ARFI imaging accurately localized and sized the lesions within the myocardium. Differences in the maximum lateral and axial dimensions were statistically below 2 mm and 1 mm respectively for the two thresholding methods, with mean percent overlap of 68.7±5.21% and 66.3±8.4% for the two thresholds used. CONCLUSION: ARFI imaging is capable of visualizing myocardial RFA lesion dimensions to within 2 mm in vitro. Visualizing lesions during transcatheter cardiac ablation procedures could improve the success of the treatment by imaging lesion line discontinuity and potentially reducing the required number of ablation lesions and procedure time.